(untitled) (Bangladesh Journal of Infectious Diseases, 2026)
Background: Physician burnout during the COVID-19 pandemic has been a significant global concern, but data from Bangladesh are limited. Objective: The purpose of the present study was to assess burnout levels and identify associated factors among physicians working in tertiary hospitals in Dhaka, Bangladesh, during the COVID-19 pandemic. Methodology: This cross-sectional study was conducted from July to December 2020 with 313 physicians from five tertiary hospitals in Dhaka, Bangladesh. Burnout was measured using the Oldenburg Burnout Inventory, which was rescaled to a 0–100 metric. Multiple linear regression analysis was performed to identify the predictors of burnout. Results: More than half of the physicians (57.5%) experienced severe burnout, while 29.7% and 12.8% had mild and moderate burnout, respectively. Female physicians reported significantly higher burnout scores than males (B = 4.17; 95% CI: 1.82–6.52; p = 0.001). Poor work–life balance (β = 0.292, p < 0.001), COVID-19–related anxiety (β = 0.214, p < 0.001), and hypertension (β = 0.131, p = 0.008) were positively associated with burnout. In contrast, higher levels of organizational (β = –0.242, p < 0.001) and social support (β = –0.276, p < 0.001) were protective factors. Younger physicians also reported more severe burnout symptoms (β = –0.128, p = 0.011). The final model explained 42.7% of the variance in burnout scores (adjusted R² = 0.412). Conclusion: Severe burnout was highly prevalent among physicians during COVID-19, with female physicians disproportionately affected. Poor work–life balance was the strongest risk factor, whereas social and organizational support was protective. Strengthening gender-sensitive interventions and institutional support is essential to safeguard physicians’ well-being and build resilience for future pandemics. Bangladesh Journal of Infectious Diseases, December 2025;12(2):285-293